Некоторые аспекты массовой кристаллизации алмаза в системе Mе–C - Лоладзе, Н.Т.; Церодзе, М.П. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2009)
The influence of such factors as the value and geometry of the metal graphite contact surface, the density and concentration of formed crystallization centers on the final result of diamond
synthesis is studied. The relation between the value of the Me – C contact surface and the number of
crystallization centers is evaluated quantitatively on the basis of experimental data; also, the properties of synthesized diamonds are studied for various schemes of arrangement of reagents in the
high pressure chamber. Detailed consideration is given to the physical meaning of such values as
the specific concentration of crystallization centers N/V and the specific density of crystallization
centers N/S. It is shown that the specific concentration of nuclei depends on the Me-C contact surface value, while their density is determined by the physical and chemical properties of metal and
graphite reagents. It is established that by varying the geometry and value of the Me-C contact surface and also by choosing appropriately a scheme of reagents arrangement it is possible to improve
essentially the technological parameters of synthesis processes in one and the same P-T conditions.